Shared Housing as Public Space? The Ambiguous Borders of Social Infrastructure - Grundström, Karin (2022)
The Folkhem era in Sweden set high architectural standards for social infrastructures dispersedly located in cities. Over the past two decades, however, Swedish planning, when it comes to the localization of social infrastructure, has been increasingly characterized by privatized social infrastructures added to housing. Methodologically, this article draws on a compilation of architectural designs of shared housing that includes social infrastructure, 12 interviews with developers, and 22 interviews with residents. The article argues, first, that two historical approaches can be identified: one in which porous borders support urban social life in and around the housing complex and another where distinct boundaries form an edge where things end. Secondly, the article argues that in recent shared housing complexes, the infrastructures of fitness, health care, and privatized services—previously available solely in the public realm—have moved physically and mentally closer to the individual, largely replacing residents’ everyday use of public space. The article concludes that in recent shared housing complexes, ambiguous borders are formed. Ambiguous borders allow a flow of goods and people, but the flow is based on the needs and preferences of residents only. Overall, such privatization counteracts the development of urban social life while adding to housing inequality, as this form of housing is primarily accessible only to the relatively wealthy. Furthermore, there is a risk that urban planning may favour such privatization to avoid maintenance costs, even though the aim of planning for general public accessibility to social infrastructure is thereby shifted towards planning primarily for specific groups.